2017
DOI: 10.3343/alm.2017.37.5.426
|View full text |Cite
|
Sign up to set email alerts
|

Human Papillomavirus Genotype Distribution Among 18,815 Women in 13 Korean Cities and Relationship With Cervical Cytology Findings

Abstract: BackgroundThe prevalence and genotype distribution of Human papillomavirus (HPV) infection vary depending on geographical region and the immunity provided by vaccines. This study aimed to clarify the recent prevalence and genotype distribution of HPV according to age and cervical cytology findings in Korea.MethodsThis study included 18,815 health examinees that underwent cervical cytology and HPV genotyping tests at 16 centers of Korean Association of Health Promotion in 13 cities in Korea, between January 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 25 publications
5
17
0
Order By: Relevance
“…In general, there are substantial differences between different countries and geographical areas in genotype distribution of HPV infections 12. As in our study, several studies have shown that types 52 and 58 are the most commonly seen high-risk HPV types in patients without any intra-epithelial lesions 3–5 10 13. Furthermore, Shen et al demonstrated in cervical pre-cancerous lesions that the general proportions for HPV52, HPV51, and HPV58 were 8.6%, 5.2%, and 7.7%, respectively 6.…”
Section: Discussionsupporting
confidence: 66%
“…In general, there are substantial differences between different countries and geographical areas in genotype distribution of HPV infections 12. As in our study, several studies have shown that types 52 and 58 are the most commonly seen high-risk HPV types in patients without any intra-epithelial lesions 3–5 10 13. Furthermore, Shen et al demonstrated in cervical pre-cancerous lesions that the general proportions for HPV52, HPV51, and HPV58 were 8.6%, 5.2%, and 7.7%, respectively 6.…”
Section: Discussionsupporting
confidence: 66%
“…Countries with existing HPV vaccination programs had already witnessed a dramatic reduction in HPV 16, the type that accounts for the majority of cervical cancer cases and other vaccine‐covered types . In settings where HPV vaccine is not available, cervical cancer screening programs are essential.…”
Section: Discussionmentioning
confidence: 99%
“…In a study carried out by Nah E-T et al, 15,426 women were analyzed. The most common high-risk HPV subtype among these patients was determined to be HPV 52 (1.9%) [ 32 ]. In some other previous studies, 100,000 women in 5 continents who have normal cytology records were examined.…”
Section: Discussionmentioning
confidence: 99%